A tale of two turnarounds at EDS : the Jordan rules - Shein, James B., 1942-; Frazzano, Rebecca; Meagher, Evan ([London] : SAGE, 2016)
The case briefly describes the history of Electronic Data Systems (EDS) under Ross Perot and GM before turning to the beginning of a tumultuous decade in the late 1990s.
Originally Published in: Shein, J., Frazzano, R., & Meagher, E. (2010). A Tale of Two Turnarounds at EDS: The Jordan Rules. 5-409-754. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Electronic Data Systems Corporation; Information technology -- Management -- Case studies; Corporate turnarounds -- Case studies